IMPLEMENTASI KURIKULUM MERDEKA DALAM PENDIDIKAN INDONESIA: KAJIAN LITERATUR - Syafriana, Dewi; Dwi Purnama Dawolo, Berlinda; Andriani Butar Butar, Leli; Batubara, Nuraina; Silitonga, Sriwindi (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This research aims to examine the implementation of the Merdeka Curriculum in Indonesian education through a literature review approach. The Merdeka Curriculum is the latest educational policy that emphasizes competency-based learning, differentiation, and strengthening the profile of Pancasila students. The research method used is a literature study by reviewing scientific articles, books, regulations, and recent research reports published between 2020 and 2025. The results of the study indicate that the Merdeka Curriculum has great potential in improving the quality of learning through flexible planning, teacher empowerment, and character development of students. However, its implementation still faces various challenges, such as the readiness of educators, limitations of facilities, and quality disparities among educational units. This article contributes to providing a comprehensive overview of the dynamics of implementing the Merdeka Curriculum while also offering recommendations for strengthening teacher capacity, equalizing facilities, and enhancing monitoring and evaluation so that this policy can be effectively implemented. Thus, this literature review is expected to serve as a reference for academics, education practitioners, and policymakers in formulating more optimal implementation strategies.